Exploring the effects of the perceived fit with corporate social responsibility on brand loyalty in the tobacco industry - Vu, Thi Kim Chi; Tran, Manh Dung (Journal of International Economics and Management, 2015)
The shifting emphasis to the dimensions of Corporate Social Responsibility (CSR) by firms has been more pronounced than ever before. Although CSR efforts by tobacco firms have been labelled oxymoron by commentators, they have still executed aggressive CSR strategies aiming at the public. With the purpose of effectively carrying out CSR practices, tobacco firms need to explore how to concentrate customers’ attention on their CSR practices, that is, the determinants influencing brand loyalty. This study considered the aspects of perceived fit between CSR activities and a firm’s core business and corporate image pertaining to brand loyalty. To analyse the relationships among them, Multiple Regression Analysis was employed with a sample of 152 United Kingdom smokers. Results show that while there is a negative relationship between the perceived fit of corporate image and CSR activities and brand loyalty, there is no support for the association between the perceived core business-CSR fit and brand loyalty in the tobacco industry.